Pertimbangan Hakim Atas Pencurian dengan Modus Carding Berdasarkan Pasal 362 KUHP Jo. Undang–undang Nomor 19 Tahun 2016 Atas Perubahan Undang-undang Nomor 11 Tahun 2008 Tentang Informasi dan Transaksi Elektronik - Agung Mahardika; Uu Idjuddin Solihin (VERITAS, 2022)
This journal discusses the consideration of judges in deciding a crime of one of the Cyber ​​Crime crimes namely Carding. Especially in the case of regulating the Carding crime, the factors of the perpetrators committing the Caeding crime, as well as the consideration of the judge in giving a verdict on the Carding crime. research conducted by studying and examining library legal materials, data collection is done by examining secondary data using primary legal data in the form of a court decision. As well as secondary data. Carding is a crime that is fairly new in Cyber ​​Crime which is a transnational crime but occupies the highest position in Indonesia compared to other Cyber ​​Crime crimes. there is no specific regulation or regulation regarding the crime of Carding despite the existence of Law Number 11 of 2018 as amended by Law Number 19 of 2016 concerning Electronic Information and Transactions and the application of Articles of the Criminal Code but are deemed inappropriate. Law enforcers often have difficulty in overcoming and mismatch in upholding in preventing Carding cases, especially judges to uphold justice which is actually proven or not proven by a defendant committing a crime based on the judge's decision. Keywords: Carding Criminal Acts, Judge Considerations